2016
DOI: 10.1007/s10826-016-0623-2
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Behaviors as Moderators for the Link between Parental Self-Efficacy and Parenting Practices

Abstract: Based on theory that parents with higher levels of self-efficacy (PSE) should find it easier to parent effectively in the face of challenging child behaviors than should parents with lower levels of PSE, this study examines the link between PSE and parenting using children’s behaviors as potential moderators. Participants were 130 parents who had an older adolescent (M age = 17.58) in addition to the target adolescent (M age = 11.79), and both adolescents’ externalizing behaviors were used as moderators for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Relationships with other family members, such as siblings, were not available to be included here, but, if included, might have shed additional light on patterns of hostility in families. For example, parents tend to differ in their parenting of children in the same family (e.g., Glatz, Cotter, & Buchanan, 2017; Glatz & Stattin, 2013; Whiteman, McHale, & Crouter, 2003), and it is possible that the interactions captured by the triadic family conflict task were not indicative of a general parental interaction style that would be the same across multiple children. In addition, sibling relationships are important for youth’s social and behavioral development, and hostile sibling interactions can spill over to hostility in peer relationships (e.g., Feinberg, Solmeyer, & McHale, 2012; Glatz, Källström, Hellfeldt, & Thunberg, in press; McHale, Whiteman, Kim, & Crouter, 2007; Patterson, DeBaryshe, & Ramsey, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Relationships with other family members, such as siblings, were not available to be included here, but, if included, might have shed additional light on patterns of hostility in families. For example, parents tend to differ in their parenting of children in the same family (e.g., Glatz, Cotter, & Buchanan, 2017; Glatz & Stattin, 2013; Whiteman, McHale, & Crouter, 2003), and it is possible that the interactions captured by the triadic family conflict task were not indicative of a general parental interaction style that would be the same across multiple children. In addition, sibling relationships are important for youth’s social and behavioral development, and hostile sibling interactions can spill over to hostility in peer relationships (e.g., Feinberg, Solmeyer, & McHale, 2012; Glatz, Källström, Hellfeldt, & Thunberg, in press; McHale, Whiteman, Kim, & Crouter, 2007; Patterson, DeBaryshe, & Ramsey, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ self‐efficacy and beliefs could affect the behaviors of their adolescent children with cancer in a positive way (Bandura, ). Self‐efficacy regarding physical activity among family childcare providers is positively associated with time provided for children's physical activity (Figueroa & Wiley, ), and higher levels of parental self‐efficacy is associated with lower levels of difficult behaviors among adolescents (Glatz, Cotter, & Buchanan, ). These findings suggest that parental self‐efficacy, in addition to that of adolescent patients themselves, might be an appropriate target for intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, more mature mothers reported less sleep-related problems for their toddlers. Glatz, Cotter, and Buchanan (2017) found that parental self-efficacy predicted promotive (i.e., positive and involved) parenting in parents of adolescents. Parental self-efficacy can be considered as a form of internal locus of control which in turn is an indicator of psychological maturity.…”
Section: Parental Personality As a Determinant Of Parentingmentioning
confidence: 97%